Parental stress and dedication to the education of their children among parents from eastern Peru - Jhomira Tucto-Claudio; Uriaz Navarro; Jessica Aranda-Turpo; Julio Cjuno (Interacciones)
Background: The parental stress levels increased during their children's virtual education season. This makes parents feel overwhelmed by the demands of the parental role, promoting negative feelings about themselves or their children. Therefore, the aim is to determine the relationship between parental stress and dedication to the virtual education of their children in parents from the city of Tingo Maria, Peru. Methods: It is a cross-sectional descriptive non-experimental design study with a correlational scope. The instruments used in the data collection were: The parental Stress Scale and the Questionnaire Dedication to the Virtual Education of their Children, in which 356 parents aged 18 to 59 years (Me=37; SD=7.49) from the Peruvian Amazon dedicated to agriculture participated. Results: Where it was found that there is no relationship between parental stress and dedication to the virtual education of children (rho = -0.096; p = 0.071). However, a highly significant relationship was found between the dimensions of parental rewards (rho = 0.384; p=0.000) and stress factors (rho = -0.270; p = 0.000) with the variable dedication to virtual education with moderate effect size and small respectively. Likewise, significant differences were found between parental stress according to marital status (U= 12056.0, p<0.05, d= 1.703) and children's dedication to virtual education according to age (U=3360.0, p<0.05, d= 1.343). Conclusions: In the parents who participated in the study, the greater the stressors, the lower the dedication to their children's virtual education, and an increase in parental reward increased the dedication to their children's virtual education. Further studies can explore the relationship of these variables in parents with other socioeconomic conditions and representative samples from other regions.